Laparoscopic management of ileal endometriosis: presented as sub-acute intestinal obstruction - Yogini, Kavitha Duraisamy; Kumari, Kalyana S.; Murthy, Sathiya R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Patients with bowel endometriosis will usually experience a long delay in getting diagnosed as the physician will always think of other medical conditions related to bowel before considering the possibility of endometriosis. Imaging studies are not sensitive enough for definite diagnosis. Bowel endometriosis can be treated by either hormone therapy or surgical therapy. Surgery should be considered in selected patients, who have severe stenosis of intestinal lumen resulting in obstruction. Small bowel endometriosis may not be accompanied by pelvic endometriosis. When the disease involves the jejunum or the ileum, it usually has a benign course, but in rare circumstances may present as an acute abdomen. Ileal endometriosis should be carefully considered in the differential diagnosis of Crohn’s disease, because bowel endometriosis frequently produces local inflammation, adhesions, stricture and angulation. A segmental bowel resection may be required to completely treat their disease. The role of postoperative administration of gonadotropin releasing hormone analogues (GnRH) to prevent disease recurrence or increase symptom free interval is not well established.